A existência humana como estrutura de horizonte e as aparições da morte na poesia de Ferreira Gullar - Jappe, Ronaldo José (2018)
The purpose of this work is to show how the elements that characterize human existence as a horizon structure and the many apparitions of death in differente moments of life are shown in Ferreira Gullar's poetry. The landscape theory, proposed by Michel Collot, which takes as support the Jean-Pierre Richard's French-based thematic critique and Merleau-Ponty's phenomenology, shows, through its structuring elements – point of view, extension, part and unity/ensemble – the way landscape becomes an object of critical reflection in dialog, mainly with literature. Once Collot considers landscape as a way of seeing, its perception –considered as an “act of thought” capable of making the synthesis of sensory data and constantly transposing them towards its horizon – will be conceived as a perception about being in the world and being in the writing, relating them to the creation of a “sense of the senses”, showing the strong bond that unites the notions of landscape and horizon, founding what Collot calls horizon structure. Through this structure and thorugh landscape's founding elements that one may understand the correpondence between horizon and subjectivity, between landscape and existence, governed by the far and near dialectic which, in turn, has an unapartable temporal and spacial meaning. This dialectic enabled the perception of the way how Gullar projects removals and approaches about death. The examination of the poet's conceptions of existence evidences the different ways he sees death in its several appearances – what allows us to interpret it as a poetic referent – in the different phases of his life. The understanding of this theme requires a study of the philosophical view on life and existence. For this intent, human existence, from its beginnings to its end, is examined in a more detailed way, presenting the view of different thinkers. Considering these theoretical reflections related to landscape and poetic referent concepts, attention is paid, in reading the texts, to the way in which recurrent themes may become a space for articulation between our desires and expectations and the reality that surrounds us, when perceiving how the poet and his work deal with the dilemmas of the existence.